Institutional framework and governance of the water sector and implications on service delivery - Raja Ariffin, Raja Noriza; Sawon, Sanisah; Abd Rahman, Nur Hairani; Hanafi, Hanira; Zahari, Rustam Khairi (e-International Publishing House, Ltd., UK, 2024)
Water governance discourses state that “water crisis is a crisis of governance”. Improving governance is critical in ensuring water security. This study examines water sector governance and institutional framework's impact on service delivery. It employs a qualitative approach with Klang Valley, Selangor as the case study. Policy actors from federal and state governments are interviewed for primary data. Secondary data includes documents and archival records. Findings show that water service delivery was hampered by unclear jurisdiction, conflicting priorities, financial constraints, and lack of political will. Overcoming these challenges can be the basis for improving water service delivery system.